2017
DOI: 10.3389/fpls.2017.02052
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Expression of Pumpkin NAC Transcription Factor CmNAC1 Improves Multiple Abiotic Stress Tolerance in Arabidopsis

Abstract: Drought, cold and salinity are the major environmental stresses that limit agricultural productivity. NAC transcription factors regulate the stress response in plants. Pumpkin (Cucurbita moschata) is an important cucurbit vegetable crop and it has strong resistance to abiotic stress; however, the biological functions of stress-related NAC genes in this crop are largely unknown. This study reports the function of CmNAC1, a stress-responsive pumpkin NAC domain protein. The CmNAC1-GFP fusion protein was transient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 62 publications
5
32
0
Order By: Relevance
“…The T1 generations were said to be the transgenic tobacco lines that contained a single insertion, whose seeds were grown in the same conditions as described earlier. After three weeks, the seedlings were transferred to a hydroponic system and two weeks later, the seedlings of the transgenic tobacco were exposed to 100 mM NaCl [ 34 ], 15% PEG-6000 ( m / v ) [ 35 ] and 100 mM H 2 O 2 [ 36 ] in half strength Hoagland’s nutrient solution (24 h) for simulating salt, drought and oxidative stress, respectively. For cold stress, the seedlings were cultivated in half strength Hoagland’s solution at 4 °C [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…The T1 generations were said to be the transgenic tobacco lines that contained a single insertion, whose seeds were grown in the same conditions as described earlier. After three weeks, the seedlings were transferred to a hydroponic system and two weeks later, the seedlings of the transgenic tobacco were exposed to 100 mM NaCl [ 34 ], 15% PEG-6000 ( m / v ) [ 35 ] and 100 mM H 2 O 2 [ 36 ] in half strength Hoagland’s nutrient solution (24 h) for simulating salt, drought and oxidative stress, respectively. For cold stress, the seedlings were cultivated in half strength Hoagland’s solution at 4 °C [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Examining water loss rate from detached leaves/rosettes has been widely used as important, reliable indicator to rapidly predict the plant water status and performance under drought conditions [53][54][55]. A great number previous studies included this tool in evaluating the performance of various transgenic plants, with the tracking of water loss rates over the course duration of 3 h [56,57], 4 h [58,59], 5 h and longer [52,60]. Upon being excised, water loss is indicated to be achieved via stomatal transpiration within the first hour followed by cuticular transpiration and residual transpiration (i.e., from incompletely closed stomata) in subsequent hours [61].…”
Section: Discussionmentioning
confidence: 99%
“…Manuscript to be reviewed 2017; Obrero et al, 2011;Tashiro et al, 2016;Niu et al, 2017) and have been used for gene expression studies in cucumber (Wang et al, 2009;Migocka and Papierniak, 2011;Warzybock and Migocka, 2013). The genes UFP (ubiquitin), EF-1A (elongation factor), PRL36aA (60S ribosomal protein L36a/L44), PP2A (protein phosphatase) and CACS (clathrin adaptor complexes medium submit family protein) have been used for reliable normalization in different experimental sets in zucchini (Cucurbita pepo) (Obrero et al, 2011), and these reference genes have been successfully applied to both cucumber and pumpkin in specific environments, including powdery mildew, salinity, cold, dehydration, H 2 O 2 , and abscisic acid (ABA) treatments (Berg et al, 2015;Cao et al, 2017;Reda et al, 2018). Unfortunately, no single reference gene has been confirmed that exhibits uniform and stable expression under different experimental conditions.…”
Section: Introductionmentioning
confidence: 99%